1968
DOI: 10.1037/h0082741
|View full text |Cite
|
Sign up to set email alerts
|

Recognition versus recall in schizophrenia.

Abstract: Twenty-four schizophrenic and 24 normal Ss, 8 in each group being overinclusive and 16 non-overinclusive, were presented with two 20-word lists, one for free recall and one for recognition. The recognition alternatives were rhymes, synonyms, and synonym-rhymes of the various target words. Schizophrenics were poorer than normals in recall but not in recognition, and the ratio of recall over recognition was significantly greater for schizophrenics than for normals. The results of an analysis of the recognition e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
46
2

Year Published

1973
1973
1993
1993

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 22 publications
5
46
2
Order By: Relevance
“…Bauman and Murray (1968) found that recognition performance of overinclusive schizophrenics was superior to that of nonoverinclusive schizophrenics. The possible relation of overinclusion to good recognition memory is interesting for two reasons: (a) it might shed light on the nature of overinclusion, and (b) a focus on cognitive benefits associated with overinclusion would be more consistent with the latter's relation to good prognosis (Payne, 1968).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Bauman and Murray (1968) found that recognition performance of overinclusive schizophrenics was superior to that of nonoverinclusive schizophrenics. The possible relation of overinclusion to good recognition memory is interesting for two reasons: (a) it might shed light on the nature of overinclusion, and (b) a focus on cognitive benefits associated with overinclusion would be more consistent with the latter's relation to good prognosis (Payne, 1968).…”
mentioning
confidence: 98%
“…Several investigators (Bauman & Murray, 1968; Koh, Kayton, & Berry, 1973;Nachmani & Cohen, 1969) have found that schizophrenics perform inadequately on recall tasks, but adequately on recognition tasks. They have used several two-process models to explain these findings (see also Bauman, 1971).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Schizophrenia is a neuropsychiatric disorder that lends itself particularly well to the study of conceptually driven processes in memory. Patients with schizophrenia have shown an impaired ability compared with normal control subjects to recall recently presented material in a variety of tasks, including serial recall, free recall, and cued recall (Bauman, 1971;Bauman & Murray, 1968;Calev, 1984;Goldberg, Weinberger, Pliskin, Berman, & Podd, 1989;Koh & Kayton, 1974;Traupmann, 1975). It is suggested that the consistent recall failure in these patients is related to deficits in the use of elaborative and organizational processes, namely conceptually driven processes.…”
mentioning
confidence: 99%
“…More recently, Bauman and Murray (3) showed that the schizophrenic memory deficit was specific to recall and that recognition was unimpaired, which supports the hypothesis that the deficit is greatest in the association-forming stage rather than in the acquisition. Bauman (2) found that schizophrenics and normals differed in the serial position of the correct responses.…”
Section: Premorbid Adjustment Andmentioning
confidence: 54%